Brief Report: Single-Cell Analysis Reveals Cell Division-Independent Emergence of Megakaryocytes From Phenotypic Hematopoietic Stem Cells. (6th August 2015) - Roch, Aline; Trachsel, Vincent; Lutolf, Matthias P.
Abstract: Despite increasingly stringent methods to isolate hematopoietic stem cells (HSCs), considerable heterogeneity remains in terms of their long-term self-renewal and differentiation potential. Recently, the existence of long-lived, self-renewing, myeloid-restricted progenitors in the phenotypically defined HSC compartment has been revealed, but these cells remain poorly characterized. Here, we used an in vitro single-cell analysis approach to track the fate of 330 long-term HSCs (LT-HSC; Lin− cKit+ Sca-1+ CD150+ CD48− CD34−) cultured for 5 days under serum-free basal conditions. Our analysis revealed a highly heterogeneous behavior with approximately 15% of all phenotypic LT-HSCs giving rise to megakaryocytes (Mk). Surprisingly, in 65% of these cases, Mk development occurred in the absence of cell division. This observation suggests that myeloid-restricted progenitors may not derive directly from LT-HSCs but instead could share an identical cell surface marker repertoire. Stem Cells 2015;33:3152–3157